2012
DOI: 10.1007/bf03325800
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of wideband high-speed railway channel in viaduct scenario at 2.35 GHz

Abstract: Abstract:In order to obtain accurate characteristics of wireless channels in the viaduct area of China, a channel measurement was taken in a railway viaduct scenario of the Zhengzhou-Xi'an passenger dedicated line with a bandwidth of 50 MHz at 2.35 GHz. The single-slope log-distance model is used to analyze the path-loss (PL), and the distribution of shadow fading (SF) is obtained by statistical methods, which shows that the normal distribution fits the samples well. Ricean K-factor is analyzed by the method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Figure shows the measured PL result and the PL model in the station scenario and compares the proposed PL model with free space model, WINNER II D2a model [ Kyösti et al ., ], and PL results in open viaduct [ Liu et al ., ], obstructed viaduct [ Guo et al ., ], cutting [ Sun et al ., ], and hilly terrain [ Luan et al ., ] environments. The fitting parameters a and n of the PL model are found to be 19.5 and 3.32, respectively.…”
Section: Large‐scale Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure shows the measured PL result and the PL model in the station scenario and compares the proposed PL model with free space model, WINNER II D2a model [ Kyösti et al ., ], and PL results in open viaduct [ Liu et al ., ], obstructed viaduct [ Guo et al ., ], cutting [ Sun et al ., ], and hilly terrain [ Luan et al ., ] environments. The fitting parameters a and n of the PL model are found to be 19.5 and 3.32, respectively.…”
Section: Large‐scale Characteristicsmentioning
confidence: 99%
“…It can be found that the RMS DS measured in the station scenario is much higher than that with the mean value of −7.4 and the standard deviation of 0.2 in the WINNER D2a model, whereas it is lower than the values in the obstructed viaduct and hilly terrain scenarios reported in Guo et al . [] and Luan et al . [].…”
Section: Small‐scale Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GEV distribution [29] appeared to be a good fit for both UWB [30] and milimeter wave [31] small-scale variations. On the other hand, the logistic family of distributions [32] has been used successfully in ray-cluster-based modelling at 5 GHz [33] and modelling the probability density function (PDF) of the rms delay spread at 2.35 GHz [34]. We have also included the normal distribution as a reference.…”
Section: Small-scale Variationsmentioning
confidence: 99%
“…The HSR propagation environment can be classified into different scenarios, including viaduct, hilly terrain, tunnel, cutting, and station [2,3]. Recently, some measurementbased studies have been carried out in viaduct [4][5][6][7], tunnel [8][9][10][11], and cutting [12,13] scenarios. Field strength results at 320 MHz band for different scenarios can be found in [14].…”
Section: Introductionmentioning
confidence: 99%